ANALISIS IKLAN, PROMOSI PENJUALAN DAN KUALITAS PRODUK PADA IMPLUSE BUYING DI SOSIAL MEDIA FACEBOOK ( STUDI KASUS KOMUNITAS DISCORD ALWAYSEASY ): Advertising; Sales Promotion; Product Quality; Impulse Buying - Sihombing, William (UNIB Press, 2023)
The purpose of this study was to analyze the effect of advertising, sales promotion and product quality onimpulse buying on the Facebook social media application. This research is a quantitative research and is acase study that explains the relationship between one variable and another. the subject of the populationconsists of several members of the population and the number of samples is 75 respondents. This studyproves that advertising and sales promotion significantly affect the occurrence of impulse buying, whileproduct quality has no significant effect on the occurrence of impulse buying. The benefits of research canbe used as a reference source for companies or individuals to use Facebook ads to advertise products orservices.